PROTECTIVE EFFECT OF URTICA DIOICA ON RENAL MORPHOMETRIC AND HISTOLOGIC ALTERATIONS IN STREPTOZOTOCIN DIABETIC RATS - MJ Golalipour (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Hyperglycemia causes renal morphometric and histological alterations. This study was done to determine the protective role of urtica dioica on renal morphometric and histological alterations in streptozotocin diabetic rats.METHODS: Thirty adult Wistar rats divided into three groups. Group I normal control group, group II: diabetic group animal received 80 mgkg STZ (streptozotocin) by intraperitoneally and group III: protective group, rats received 100 mg/kg daily hydroalcoholic extract of U. dioica for 5 days then diabetes induced in animals by STZ. In the end of five weeks the animals had been scarified, the kidneys fixed by buffer formaldehyde, processed, sectioned and stained with H;E. FINDINGS: Mean of blood glucose concentrations in end of fifth weeks were 99.4, 454.7 and 303.6 in control, diabetic and protective groups, respectively (p<0.05), that was lower in protective group than diabetic group. Ration of kidney/body weight in control, diabetes and protective group were 0.42, 0.51 and 0.48, respectively (p<0.05). Glomerular area in control, diabetes and protective group were 1335.3, 1441.8 and 1326.4 µm2, respectively (p<0.05). Glomerular diameter in diabetic group (162.2 µm) was higher than control (156.1) and protective group (153.2). Pathology finding as glomerular sclerosis was seen in diabetic group but this finding did not observe in control and protective groups.CONCLUSION: This study demonstrated that administration of urtica dioica before streptozotocin-induced diabetes has protective effects on blood glucose, renal morphometric and histological alterations in streptozotocin diabetic rats.